2023
DOI: 10.3389/fimmu.2023.1171811
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a ubiquitination-related gene signature associated with prognosis in pancreatic duct adenocarcinoma

Abstract: BackgroundPatients with pancreatic duct adenocarcinoma (PDAC) have varied prognoses that depend on numerous variables. However, additional research is required to uncover the latent impact of ubiquitination-related genes (URGs) on determining PDAC patients’ prognoses.MethodsThe URGs clusters were discovered via consensus clustering, and the prognostic differentially expressed genes (DEGs) across clusters were utilized to develop a signature using a least absolute shrinkage and selection operator (LASSO) regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Currently, there is insufficient research on URGs in patients with liver cancer. Some previous studies have confirmed the prognostic role of URGs in certain cancers, such as pancreatic cancer and prostate cancer [ 53 , 54 ]. The research validated the prognostic significance of URGs in liver cancer and investigated the potential use of immunotherapy, offering valuable guidance for tailored clinical interventions.…”
Section: Discussionmentioning
confidence: 80%
“…Currently, there is insufficient research on URGs in patients with liver cancer. Some previous studies have confirmed the prognostic role of URGs in certain cancers, such as pancreatic cancer and prostate cancer [ 53 , 54 ]. The research validated the prognostic significance of URGs in liver cancer and investigated the potential use of immunotherapy, offering valuable guidance for tailored clinical interventions.…”
Section: Discussionmentioning
confidence: 80%
“…The relevance between ADH5 and immune cell infiltration in KIRC was investigated by the TIMER analysis tool ( https://cistrome.shinyapps.io/timer/ ). The ESTIMATE method utilizes existing gene expression profiles to estimate the degree of infiltration of stromal or immune cells into the tumor [ 16 ]. So, based on the ADH5 expression matrix, we executed the ESTIMATE algorithm to calculate the immune, stromal, and ESTIMATE scores.…”
Section: Methodsmentioning
confidence: 99%